2017
DOI: 10.3151/jact.15.300
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Curing Conditions on Properties of Normal and High Strength Concrete with and without Pre-Wetted Lightweight Aggregates

Abstract: This paper presents the results of an experimental study conducted to evaluate the effect of curing conditions on the properties of normal and high strength concrete (NSC and HSC) with and without pre-wetted lightweight aggregates (LWAs). Cylinder specimens were drilled out from square concrete slabs subjected to four curing regimes (i.e. standard, water, natural and sealed curing) respectively, and then tested to obtain the compressive strength after 60 days. Three discs cut along the height direction of cyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…This may be due to the fact that over time the free water in concrete mixes under air-dry uncontrolled curing evaporated and the trapped water molecules in LECA were given back to the empty capillary pores to react with cement particles and complete the hydration process at older ages ( Fig. 7), similarly to what Wang et al [57] reported. The fibres content has no effect on the hydration process of concrete materials.…”
Section: Compressive Strengthsupporting
confidence: 64%
See 2 more Smart Citations
“…This may be due to the fact that over time the free water in concrete mixes under air-dry uncontrolled curing evaporated and the trapped water molecules in LECA were given back to the empty capillary pores to react with cement particles and complete the hydration process at older ages ( Fig. 7), similarly to what Wang et al [57] reported. The fibres content has no effect on the hydration process of concrete materials.…”
Section: Compressive Strengthsupporting
confidence: 64%
“…Wang et al [57], while the external water vapour particles in the 90 °C vapour curing are much less dense than those of external liquid water as reported by Firestone [73]; thus, they can easily penetrate the concrete specimens in depth as seen in Fig. 8.…”
Section: Compressive Strengthmentioning
confidence: 85%
See 1 more Smart Citation